The mediating role of intrinsic motivation in the relationship between external support and performance goals among Chinese high school students: The moderating effect of gender - Xinyi Tian; Yue Zhang (Acta Psychologica)
Understanding the mechanisms that shape high school students' performance goals is crucial for fostering their academic development. Despite growing interest in the role of social support and motivation, limited research has examined how perceived teacher and parental support jointly influence performance goals through internal psychological processes, particularly in large-scale non-Western samples. Addressing this gap, the present study investigates the mediating role of intrinsic motivation and the moderating role of gender in the relationship between social support and performance goals. A cross-sectional survey was conducted among 11,900 second-year high school students from a central province in China. Data were analyzed using structural equation modeling (SEM). Results indicated that both perceived teacher support and perceived parental support significantly and positively predicted students' performance goals. Importantly, intrinsic motivation partially mediated these relationships, with a stronger mediating effect observed in the teacher support pathway. Multi-group analyses further revealed a significant moderating effect of gender, such that the indirect effect of teacher support on performance goals via intrinsic motivation was more pronounced for female students. These findings contribute to the theoretical understanding of how social-contextual factors and motivational processes interact to shape performance goal orientation. Practical implications are discussed for developing gender-sensitive, motivation-enhancing strategies in secondary education.